ASSESSMENT OF VARIABILITY IN GRAIN YIELD, SEED MORPHOMETRIC AND VIGOUR TRAITS OF EARLY MATURING HYBRID MAIZE - Ogunniyan, Dotun; Makinde, Solomon; Adetumbi, Johnson; Olasoji, Julius (Journal of Agricultural Sciences (Belgrade), 2021)
Breeding for yield and quality requires an assessment of the seed metrics and vigour traits. This study, therefore, assessed the variability and inter-dependence of grain yield (GY), seed morphometric and vigour in early maturing hybrid maize. Seeds of 75 hybrid maize were evaluated for morphometric and quality in four replicates. A field trial laid out in randomized complete block design with three replicates was also conducted on the hybrids in Ibadan, Nigeria. Data were taken on the grain yield, seed dimension and quality parameters and subjected to analysis of variance. Least Significant Difference was used to separate groups of means. Relationships among the GY, seed morphometric and vigour traits were determined using correlation coefficients while principal component (PC) analysis was performed for variability among the hybrids. Significant differences (P
Keywords: Eigenvalues, electrical conductivity, maize yield, seed metrics, seed vigour